Decorin Mimic Regulates Platelet-Derived Growth Factor and Interferon-γ Stimulation of Vascular Smooth Muscle Cells - Scott, Rebecca A. (American Chemical Society, 2014)
[Image: see text] Following balloon injury, smooth muscle cells (SMCs) serve as targets for many of the pro-inflammatory and pro-fibrotic factors, including platelet-derived growth factor (PDGF) and interferon-γ (IFN-γ) released from activated inflammatory cells and platelets. Previously, our lab designed a mimic of the proteoglycan decorin, termed DS-SILY(20), that suppressed vascular SMC proliferation, migration, and protein synthesis in vitro, and injured vessels treated with DS-SILY(20) demonstrated reduced hyperplasia in vivo. Here we characterize the effects of DS-SILY(20) on modulating PDGF and IFN-γ stimulation in both proliferative and quiescent human SMCs to further evaluate the potential impact of DS-SILY(20)-SMC interaction on restenosis. Nanomolar dissociation constants were observed between DS-SILY(20) and both PDGF and IFN-γ. PDGF significantly increased migration, proliferation, and protein and cytokine expression, as well as increased ERK-1/2 and p38 MAPK phosphorylation in both quiescent and proliferative cultures. However, DS-SILY(20) inhibited these increases, presumably through sequestration of the PDGF. Consistent with the complex responses seen with IFN-γ in SMC physiology in the literature, the response of SMC cultures to IFN-γ was variable and complex. However, where increased activity was seen with IFN-γ, DS-SILY(20) attenuated this activity. Overall, the results suggest that DS-SILY(20) would be an ideal alternative to traditional therapeutics used and may be an effective therapy for the prevention of intimal hyperplasia after balloon angioplasty.